Isolation and Identification of Chlorophyll from Pandan Leaf Extract Using Column Chromatography - Asmarani, Bening Putri (Ad-Dawaa : Journal of Pharmacy, 2024)
Pandan is a plant whose leaves are often used by some people as an additional ingredient in food, especially as a natural dye and aromatizer. Pandan has green leaves due to the presence of chlorophyll in the leaves. Chlorophyll has benefits as an anti-cancer and is useful in cancer treatment therapy. Because pheophytin is able to activate radical compounds that are harmful to cells, this therapy is called photodynamic therapy. The purpose of this study was to isolate and identify chlorophyll in pandan leaf extract by column chromatography method using a combination of chloroform, ethyl acetate and ethanol eluents, with three variations of eluent, namely: Eluent I chloroform: ethyl acetate: ethanol (80:5:15), Eluent II chloroform: ethyl acetate: ethanol (85:10:5) and Eluent III chloroform: ethyl acetate: ethanol (90:5:5). The research stage was carried out by preparing test samples from pandan leaf ethanol extract, then isolation was carried out. Testing was carried out by column chromatography method to separate chlorophyll compounds, the isolate obtained was then identified for the presence of chlorophyll by uv-vis spectrophotometry method to determine the maximum peak at a wavelength of 665 nm. Based on the results of the study, the ethanol extract of pandan leaves was green in color and had a distinctive aroma of pandan leaves as much as 90 ml. The elution results obtained a green band suspected of being chlorophyll obtained as much as 30 ml with an elution time of 3 minutes 52 seconds. The results of the identification test with uv-vis spectrophotometry obtained a maximum wavelength at a wavelength of 665 nm and an absorbance value of 0.550. From the results of the study, it can be concluded that pandan leaf juice contains chlorophyll compounds and can be isolated by column chromatography method with a mixture of chloroform, ethyl acetate and ethanol eluents.